(untitled) (AYUSHDHARA, 2020)
In Ayurveda classics it is pointed out that cow’s milk have Vamaka, Virechaka, Sarama and Abhisyandi properties. In classics, it has been mentioned that cow milk should always be processed with Laghupanchmoola before it is consumed. Aims and Objectives of the study: To study Aetiopathogensis of cow milk protein allergy and to evaluate the efficacy of Laghupanchmoola sadhit cow milk in CMPA. Material & Methods: To fulfill the above Aims and Objectives: Total 35 patients were selected between the age group of 0-3 years of age with symptoms of CMPA. Hb%, complete history and elimination-challenge test were used for evaluation of the patients. Laghupanchmoola granules dose depend upon age and duration of trial was 60 days. Results: After analyzing the data statistically in 30 patients, statistically highly significant improvements were found in diarrhea, abdominal pain, respiratory difficulty and vomiting. Significant improvements were found in dermatitis. No improvement was found in anemia and nausea. Statistically highly significant improvement was found in weight, height, mid arm circumference, chest circumference and head circumference. After full observation of treatment modules, it was found that: Number of patient with complete improvement was 0, Number of patient unchanged was 2 (6.5%), Mild improvement was observed in 05 patients (16.6%), and Moderate improvement was observed in 21 patients (70%), where marked improvement was observed in 2 patients (6.7%). Conclusion: Laghupanchmoola proved quite effective in managing the patients of CMPA due to its Tridoṣahar, Deepana, Aamdoshanasaka, Balya and Brahmanna properties.